A Biblical Approach to Addressing the Challenges of Puberty in Adolescents Aged 9-14 Based on Psalm 119:9 - Gunawan, Nalita; Paulus, Yanto (Jurnal Teologi dan Pelayanan Kerusso, 2024)
This study addresses the challenges faced by adolescents aged 9-14 during puberty, including physical, emotional, and psychological changes. Many adolescents struggle to maintain morality in accordance with their faith-based values. Psalm 119:9 poses the question of how a young person can keep their way pure, providing a foundation for a biblical approach to help adolescents navigate the turbulence of puberty. The purpose of this study is to explore the application of a biblical approach based on Psalm 119:9 in addressing the issues of puberty. The study offers theological and practical perspectives for parents, teachers, and church leaders in guiding adolescents. The research method used is a literature review with a qualitative approach and biblical text analysis, specifically of Psalm 119:9. Surveys and interviews with parents, religious teachers, and adolescents were conducted to gather empirical data on the application of biblical principles. The findings indicate that a deep understanding of Psalm 119:9 helps adolescents align their behavior with biblical teachings. This approach can serve as an effective tool in helping adolescents maintain moral integrity amidst modern challenges. In conclusion, the biblical approach based on Psalm 119:9 is relevant in guiding adolescents through puberty and reinforcing their morality according to Christian faith teachings.